Fabrication of multi-level photoresist patterns in one-step lithography by using Cr/Ni multi-film thickness mask - Narongchai Siwarakrangsun (2018)
The 3-D microstructure can be formed by using Multi-film thickness mask (MFT-mask) with single exposure and single develop. The intensity of the UV light getting through the mask increases as the thickness of the chromium film decreases. However, the ultra-thin Cr film makes the deposition and etching process of Cr film difficult to control. By depositing the nickel film as a buffer layer on the Cr film, the Cr/Ni film stack can filter the UV light and increase the amount step of the light intensity. This can improve the performance of the MFT-mask to generate fine 3-D patterning step similar to gray-scale lithography with lower cost. © (2013) Trans Tech Publications, Switzerland.